Whoever was Narrated by the Group Except Imam Al-Bukhari - Abd , Muyasir (Islamic Sciences Journal, 2023)
ABSTRACT This research, which is entitled: (whoever was narrated by the group except Imam Al-Bukhari), is considered one of the important researches related to the Sahih of Imam al-Bukhari, in which the researcher clarified the singularities that Imam al-Bukhari singled out from the rest of the six imams. He did not narrate about some of the svientists because they violated his conditions which he has stipulated in his Sahih book. The research was divided into two sections, the first section of which was known by Imam Al-Bukhari, his book, and his conditions, and in the second section he mentioned some scholars who were not narrated by Imam Al-Bukhari except the group.